2016
DOI: 10.18632/oncotarget.11865
|View full text |Cite
|
Sign up to set email alerts
|

Novel tumor suppressor microRNA at frequently deleted chromosomal region 8p21 regulates Epidermal Growth Factor Receptor in prostate cancer

Abstract: Genomic loss of chromosome (chr) 8p21 region, containing prostate-specific NKX3.1 gene, is a frequent alteration of the prostate cancer (PCa) oncogenome. We propose a novel, paradigm shifting hypothesis that this frequently deleted locus is also associated with a cluster of microRNA genes- miR-3622a/b- that are lost in PCa and play an important mechanistic role in progression and metastasis. In this study, we demonstrate the role of miR-3622b in prostate cancer. Expression analyses in a cohort of PCa clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
5
20
0
Order By: Relevance
“…in the cytoplasm and nucleoplasm, and reduced protein level in the nuclear matrix. 33 These findings suggest that the expression of exon 37,38 This triggered our interest to explore the association between the CNA status of PDLIM2 and its expression in ESCC. Using data in TCGA-ESCC, we found that PDLIM2 gene-level deletion is frequent and is associated with decreased gene expression, suggesting that DNA copy loss might be a mechanism of its down-regulation.…”
Section: Deletion Of This Domain Results In Increased Accumulation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…in the cytoplasm and nucleoplasm, and reduced protein level in the nuclear matrix. 33 These findings suggest that the expression of exon 37,38 This triggered our interest to explore the association between the CNA status of PDLIM2 and its expression in ESCC. Using data in TCGA-ESCC, we found that PDLIM2 gene-level deletion is frequent and is associated with decreased gene expression, suggesting that DNA copy loss might be a mechanism of its down-regulation.…”
Section: Deletion Of This Domain Results In Increased Accumulation Ofmentioning
confidence: 99%
“…Some of the previously observed CNAs include amplification of 11q13.3 ( FGF4 ), 3p26.33 ( SOX2OT ), 8q24.21 ( MYC ), 14q21.1 ( FOXA1 ) and deletion of 9p21.3 ( CDKN2A ) . Some tumour suppressor genes in 8p21 were down‐regulated as a result of deleted chromosomal region, such as BNIP3L in breast and ovarian cancer and NKX3.1 and miR‐3622b in prostate cancer . This triggered our interest to explore the association between the CNA status of PDLIM2 and its expression in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…A focused objective of our research is to understand the mechanistic role of this frequently deleted genomic region in PCa progression and metastasis. Toward this, we have proposed and validated a novel hypothesis that this region is associated with a set of microRNA genes-miR-3622a, miR-3622b miR-383-that play important causal roles in PCa progression, recurrence and metastasis (19)(20)(21). MicroRNAs (miRNAs) are small, endogenous RNAs that suppress gene expression post transcriptionally via sequencespecific interactions with the 3′-untranslated regions (3′-UTRs) of cognate mRNA targets (22).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported a tumor suppressive role of miR-3622b in PCa via its regulation of epidermal growth factor receptor. 37 Towards deciphering the regulatory role of this miRNA cluster in PCa, we explored the role of miR-3622a in the present study and discovered its important regulatory role in PCa EMT. miR-3622a is a recently discovered miRNA gene that has not been studied.…”
mentioning
confidence: 99%